The impact of a clinical training unit on integrated child health care in Mexico - Guiscafré Héctor; Martínez Homero; Palafox Miguel; Villa Sofía; Espinosa Patricia; Bojalil Rossana; Gutiérrez Gonzalo (The World Health Organization, 2001)
This study had two aims: to describe the activities of a clinical training unit set up for the integrated management of sick children, and to evaluate the impact of the unit after its first four years of operation. The training unit was set up in the outpatient ward of a government hospital and was staffed by a paediatrician, a family medicine physician, two nurses and a nutritionist. The staff kept a computerized database for all patients seen and they were supervised once a month. During the first three years, the demand for first-time medical consultation increased by 477% for acute respiratory infections (ARI) and 134% for acute diarrhoea (AD), with an average annual increase of demand for medical care of 125%. Eighty-nine per cent of mothers who took their child for consultation and 85% of mothers who lived in the catchment area and had a deceased child received training on how to recognize alarming signs in a sick child. Fifty-eight per cent of these mothers were evaluated as being properly trained. Eighty-five per cent of primary care physicians who worked for government institutions (n = 350) and 45% of private physicians (n = 90) were also trained in the recognition and proper management of AD and ARI. ARI mortality in children under 1 year of age in the catchment area (which included about 25 000 children under 5 years of age) decreased by 43.2% in three years, while mortality in children under 5 years of age decreased by 38.8%. The corresponding figures for AD mortality reduction were 36.3% and 33.6%. In this same period, 11 clinical research protocols were written. In summary, we learned that a clinical training unit for integrated child care management was an excellent way to offer in-service training for primary health care physicians.